A Pattern Analysis on Goods Purchase Relationship for Minimarket’s Customers by Using Association Rule - Market Basket Analysis Method (AR-MBA) - Agus Hindarto Wibowo; Hasyrani Windyatri; Andivas Marulan; Dimaz Harits; Davin Nugraha (Journal of Information Technology Ampera, 2023)
Nowadays, technology has been rapidly developed, while data has become the most valuable component to be processed to produce useful information. Technology is very helpful for analyzing data clearly or in more detail. The implementation of this technology can be found in real governmental, social, and business activities, for example in business activity, it is indicated by the number of minimarkets spread across Indonesia. Thus, it makes business competition highly increased. Therefore, it is necessary to conduct a study by utilizing the existing data to compete. This study used the Association Rule-Market Basket Analysis method to determine customers’ interest patterns when shopping. The results of this study indicated that there were 2 rules that showed the highest confidence value, such as 63% (food and beverages) and 58% (cigarettes and drinks). Regarding these results, the minimarket can determine the next steps that should be conducted, such as setting up the layout and so on.